Phytoplankton control by stocking of filter-feeding fish in a subtropical plateau reservoir, southwest China - Zhang, Chaoshuo; Mei, Feng; Luo, Bin; Zhang, Dongxu; Cheng, Xinyu; Xiong, Yongying; Bao, Jianghui; Duan, Rui; Jiang, Hao; Jeppesen, Erik; Duan, Ming (Frontiers in Marine Science, 2023)
Stocking of filter-feeding fish (mainly Hypophthalmichthys molitrix and Aristichthys nobilis) is a common method used in lakes and reservoirs in (sub)tropical China to control phytoplankton, but the results are ambiguous and lack long-term data to support. We analysed a decade (2010-2020) of monitoring data from a subtropical plateau reservoir, southwest China, to which filter-feeding fish were stocked annually. We found that the total phytoplankton biomass, cyanobacteria biomass and average individual mass of phytoplankton decreased significantly during the study period despite absence of nutrient concentration reduction. However, the grazing pressure of zooplankton on phytoplankton also decreased markedly as judged from changes in the ratio of zooplankton biomass to phytoplankton biomass and Daphnia proportion of total zooplankton biomass. This is likely a response to increasing predation on zooplankton by the stocked fish. Our results also indicated that water temperature, total phosphorus and water level promoted phytoplankton growth. Our results revealed that filter-feeding fish contributed to the decline in the biomass of phytoplankton but that it also had a strong negative effect on the grazing pressure of zooplankton on phytoplankton, even in this deep reservoir where zooplankton may have a better chance of survival through vertical migration. The particular strong effect on zooplankton is most likely due to imbalance of stocking and harvesting of fish. In the management of eutrophic reservoirs, the reduction of external nutrient loading should have highest priority. In highland (low temperature) deep-water eutrophic reservoirs, stocking of filter-feeding fish may help to control filamentous phytoplankton provided that the fish stocking is properly managed. The optimal stocking intensity of filter-feeding fish that can help control phytoplankton in such reservoirs without excessive impact on large-bodied zooplankton is a topic for further elucidation, however.